Teilhard de chardin and the latin school of evolution: complexity, moving towards and equilibriums of nature - Galleni, Ludovico (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Teilhard de Chardin represents the best example of fruitful connections between science and theology of the XX century 1. Scientist, his fields of research were geology, palaeontology and palaeoanthropology. Man of faith he was apriest and a Jesuit. So far he had also a good training in philosophy and theology. As a scientist he accomplished his doctoral degree in Paris, under the supervision of Marcellin Boule [...].